The complete chloroplast genome of Zanthoxylum stenophyllum Hemsl. (Rutaceae), a traditional Chinese medicinal plant - Qinqin Huang; Xia Liu; Chong Sun; Haowen Liu; Houlin Zhou; Fengting Huang; Han Liu; Zexiong Chen (Mitochondrial DNA. Part B. Resources, 2022)
Zanthoxylum stenophyllum Hemsl., a type species for the genus Zanthoxylum (Rutaceae), is a traditional medicinal plant. We studied the complete chloroplast genome of this species using BGISEQ-500 platform. The chloroplast genome was 158,314 bp in size with a GC content of 38.45%. The genome contained two short inverted repeat (IRa and IRb) regions of 27,052 bp, a large single-copy region (LSC, 86,029 bp) and a small single-copy region (SSC, 18,181 bp). The annotated complete chloroplast genome contains 133 distinct genes, including 88 protein-coding genes, 37 transfer RNAs (tRNAs), and 8 ribosomal RNAs (rRNAs). Phylogenetic analysis indicated that Z. stenophyllum is clustered with Z. schiniflium and Z. pinnatum in the same branch with 100% bootstrap support. This complete chloroplast genome provides valuable genomic information for the molecular phylogeny and sustainable utilization of Zanthoxylum.